The investigation of back-transformation mechanisms of ringwoodite and majorite in the Yamato 75267 H6 - Fukimoto, Kanta; Miyahara, Masaaki; Sakai, Takeshi; Ohfuji, Hiroaki; Naotaka, Tomioka; Kodama, Yu; Ohtani, Eiji; Yamaguchi, Akira (2019)
The Tenth Symposium on Polar Science/Special session: [OA] Antarctic meteorites, Thur. 5 Dec. / 3F Multipurpose conference room, National Institute of Polar Research conference object